Priority effects of overwintered Rana tadpoles on larval Southern toad (Bufo terrestris Bonnaterre) - Hernandez, Jason P. (East Carolina University, 2010)
In natural ecosystems, the order of species arrival can impact the development of the community. In the Atlantic Coastal Plain of the Carolinas, wetland ponds exhibit a wide range of hydroperiods, ranging from ponds that dry up in late summer, to those that persist through fall and winter into spring. Ponds that persist through the fall and winter can be colonized by late-summer breeding southern leopard frogs, whose tadpoles must remain in the ponds until the following spring. Tadpoles of spring-breeding anurans, including Southern toads, are adversely affected by the presence of large tadpoles from the prior summer. I examined several mechanisms potentially responsible for this effect: overwintering tadpoles changing the environment during the winter; large tadpoles outcompeting small hatchling tadpoles; interspecific differences in competitive ability between leopard frog and Southern toad; and density-dependent effects. Leopard frog tadpoles had their primary adverse effect on Southern toads through processes occurring during the winter, prior to the arrival of Southern toads. The other mechanisms tested were not significant. The algal resource on which both species depend also showed a response to the presence of overwintered leopard frog tadpoles, being reduced where tadpoles had been present through winter and spring, and increased where overwintered tadpoles were present only in spring. This response did not become apparent until late in the spring, suggesting that resource depletion per se is not the mechanism at work, but that some other process occurring in winter leads to adverse conditions for spring-hatched tadpoles where overwintered tadpoles are present through winter. Because isolated wetlands often do not receive the same level of protection as wetlands connected to navigable waters, important amphibian habitat is often altered by humans in ways that change its habitat value. In managing for optimum biodiversity, it is important to consider the often conflicting needs of different species, and to conserve a range of different pond types of varying hydroperiods and degrees of connectivity.
Keywords: Biology, Ecology; Ecology; Wetland ecology--North Carolina; Bufonidae--North Carolina; Leopard frogs--North Carolina; Tadpoles--North Carolina